Financial Crisis – from the US to the EU - Sorin Cristian Niţă (Romanian Economic Journal, 2018)
The origins of the financial crisis that created chaos in the entire world starting with the year 2007 were the speculative bubbles that interacted with new types of financial innovations that aided in hiding different financial risks. This paper aims to analyze this phenomenon and the transmission mechanism from the starting point (US) towards the EU.